Comparative transcriptomic and proteomic analysis of yellow shell and black shell pearl oysters, Pinctada fucata martensii - Meng Xu (BMC Genomics, 2019)
Abstract Background The pearl oyster Pinctada fucata martensii (Pfu.), widely cultured in the South China Sea, is a precious source of sea pearls and calcifying materials. A yellow shell variety of Pfu. was obtained after years of artificial breeding. To identify differentially expressed genes between yellow shell and normal black shell pearl oysters, we performed transcriptomic sequencing and proteomic analyses using mantle edge tissues. Results A total of 56,969 unigenes were obtained from transcriptomic, of which 21,610 were annotated, including 385 annotated significant up-regulated genes and 227 significant down-regulated genes in yellow shell oysters (| log2 (fold change) | ≥2 and false discovery rate < 0.001). Tyrosine metabolism, calcium signalling pathway, phototransduction, melanogenesis pathways and rhodopsin related Gene Ontology (GO) terms were enriched with significant differentially expressed genes (DEGs) in transcriptomic. Proteomic sequencing identified 1769 proteins, of which 51 were significantly differentially expressed in yellow shell oysters. Calmodulin, N66 matrix protein, nacre protein and Kazal-type serine protease inhibitor were up-regulated in yellow shell oysters at both mRNA and protein levels, while glycine-rich protein shematrin-2, mantle gene 4, and sulphide: quinone oxidoreductase were down-regulated at two omics levels. Particularly, calmodulin, nacre protein N16.3, mantle gene 4, sulphide: quinone oxidoreductase, tyrosinase-like protein 3, cytochrome P450 3A were confirmed by quantitative real-time PCR. Yellow shell oysters possessed higher total carotenoid content (TCC) compared than black shell oyster based on spectrophotography. Conclusions The yellow phenotype of pearl oysters, characterised by higher total carotenoids content, may reflect differences in retinal and rhodopsin metabolism, melanogenesis, calcium signalling pathway and biomineralisation. These results provide insights for exploring the relationships between calcium regulation, biomineralisation and yellow shell colour pigmentation.